Warunkowe zawieszenie wykonania kary po nowelizacji k.k. i k.k.w. — z perspektywy zadań kuratora sądowego - Niewiadomska-Krawczyk, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article refers to the changes of regulations in Polish penal law connected with conditional suspension of sentence and execution of such sentence. The paper describes the main problems that may occur during execution of such sentences by probation officers.
Keywords: kurator sądowy; warunkowe zawieszenie; pozbawienie wolności w zawieszeniu